PENILAIAN RISIKO BENCANA KAWASAN PARIWISATA PANTAI SAYUNG, KABUPATEN DEMAK - Achmad Andi Rif’an; Agatia Wenan Tyawati (Pringgitan, 2020)
Sayung Tourist Area is located in the coastal area of Sayung District. This area consists of 3 tourist attractions: Morosari Beach, Mangrove Forest, and Tomb of Sheikh Mudzakir. Since several years this tourist area has experienced two natural disasters, namely tidal flood and coastal abrasion. This research aims to identify disaster hazards; identify vulnerabilities; identify the capacity of the community to deal with disasters; carry out risk assessments of rob and coastal abrasion in the Sayung tourist area; and suggests the direction for tourism development based on disaster risks in the area. Disaster risks assessment is conducted through several stages: first is to carry out disaster threat analysis, second vulnerability analysis, third capacity analysis, then to assess the risks of the Sayung Beach area which in this study is called multi-risks because it consists of more than one disasters. The last step is to analyze the direction of the development of tourist attractions based on the disaster analysis that has been carried out. Based on the disaster risk assessment that has been conducted, which includes hazard assessment, vulnerability assessment, and community capacity assessment, there are several areas that have a high risk of disasters, but some are low risk. All of the tourist attractions on the Sayung coast are all at high risk of disaster. The direction for the development of the area is to carry out the adaptation and mitigation strategies against tidal flood and abrasion.Keywords: Tourism Area, Beach, Disaster Risk, Sayung Beach